Genetic characteristics of the diploid offsprings in potato Cooperation 88 induced by diploid donor IVP101 - Wang, Rongyan; Feng, Yan; Peng, Jing; Tan, Chen; Zhou, Jian; Hai, Yang; Luo, Youwei; Hao, Dahai; Li, Canhui; Tang, Wei (Frontiers in Plant Science, 2024)
Diploid lines (2n = 2x = 24) derived from tetraploid potato cultivars have been utilized to hybridize with wild diploid potato species, yielding fertile offsprings. Utilizing the pollen of Solanum tuberosum Group Phureja, such as IVP101, IVP35 and IVP48, as an inducer for wide hybridization with tetraploid cultivars represents a common method for producing diploids. In this study, we created a distant hybridization induced population of tetraploid potato cultivar Cooperation 88 (C88) and IVP101, and screened all diploids using flow cytometry and ploidyNGS. We investigated the genetic composition of chloroplast and nuclear genomes in 43 diploid offsprings. We found that all diploid offsprings share the same chloroplast genomic sequence as C88 and no evidence of paternal chloroplast inheritance was found. Used SNP data to calculate the theoretical introgression index of IVP101 with diploid offsprings. The results showed that the inducer’s nuclear genome was involved in the nuclear genome of the diploid offsprings with purple stem trait, indicating that the inducer nuclear genome was not completely eliminated in the nuclear genome during distant hybridization. Furthermore, we conducted a comparative analysis of the chloroplast genomes of the Solanum genus. The results indicated that (1) the chloroplast genome sizes of the 14 Solanum species ranged from 154,289 bp to 155,614 bp, with a total number of genes ranging 128-141, and with ycf1 and rps19 pseudogenes appearing at the IRB/SSC and IRA/LSC boundaries, respectively; (2) eight divergent hotspots distributed in the LSC and SSC regions of the Solanum chloroplast genomes were identified; (3) positive selection was detected in the clpP, rbcL, rps15, and rps4 genes, likely contributing to the adaptation of Solanum species to different habitats. These results reveal the variation and evolutionary characteristics of chloroplast genomes in Solanum plants.